Pengaruh Media Pembelajaran Digital Terhadap Motivasi Belajar Siswa: Analisis Jurnal - Hesti Herawati Siagian; Ria Agustina Sigiro; Pintar Rohsangapta Padang; Ade Asminaria Sihombing; Revita Yuni (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to examine the impact of digital learning media on students' motivation by analyzing findings from various credible journal articles. As technology advances, digital tools have become a crucial component of modern education. The research employs a systematic literature review method, synthesizing empirical evidence from recent educational journals. The results indicate that digital learning media—such as e-learning platforms, educational videos, interactive applications, and digital simulations—significantly enhance students' motivation by providing dynamic, engaging, and accessible learning experiences. However, its effectiveness depends on factors like teachers' technological proficiency, infrastructure availability, and students' readiness for digital-based learning. The study concludes that while digital learning media holds great potential in boosting motivation, its successful implementation requires appropriate teaching strategies and adequate support systems.